Development of a Computerized Device for Evaluating Vestibular Function in Locomotion: A New Evaluation Tool of Vestibular Hypofunction - Chen, Po-Yin; Chou, Li-Wei; Jheng, Ying-Chun; Huang, Shih-En; Li, Lieber Po-Hung; Yu, Chung-Huang; Kao, Chung-Lan (Frontiers in Neurology, 2020)
To evaluate vestibular function in the clinic, current assessments are applied under static conditions, such as with the subject in a sitting or supine position. Considering the complexities of daily activities, the combination of dynamic activities, dynamic visual acuity (DVA) and postural control could produce an evaluation that better reflects vestibular function in daily activities. OBJECTIVE: To develop a novel sensor-based system to investigate DVA, walking trajectory, head and trunk movements and the chest-pelvis rotation ratio during forward and backward overground walking in both healthy individuals and patients with vestibular hypofunction. METHODS: Fifteen healthy subjects and 7 patients with bilateral vestibular hypofunction (BVH) were recruited for this study. Inertial measurement units were placed on each subject’s head and torso. Each subject walked forward and backward for 5 meters twice with 2 Hz head yaw. Our experiment comprised 2 stages. In stage 1, we measured forward (FW), backward (BW), and medial-lateral (MLW) walking trajectories; head and trunk movements; and the chest-pelvis rotation ratio. In stage 2, we measured standing and locomotion DVA (loDVA). Using Mann-Whitney U test, we compared the abovementioned parameters between the 2 groups. RESULTS: Patients exhibited an in-phase chest/pelvis reciprocal rotation ratio only in FW. The walking trajectory deviation, calculated by normalizing the summation of medial-lateral swaying with 1/2 body height (%), was significantly larger (FW mean±standard deviation: 20.4±7.1% (median (M)/interquartile range (IQR): 19.3/14.4-25.2) in healthy vs. 43.9 ± 27. 3% (M/IQR: 36.9/21.3-56.9) in patients, p=0.020)/(BW mean±standard deviation: 19.2 ± 11.5% (M/IQR: 13.6/10.4-25.3) in healthy vs. 29.3 ± 6.4% (M/IQR: 27.7/26.5-34.4) in patients, p=0.026), and the walking DVA was also significantly higher (LogMAR score in the patient group (FW LogMAR: rightDVA: mean±standard deviation: 0.127±0.081 (M/IQR: 0.127/0.036-0.159) in healthy vs. 0.243±0.101 (M/IQR: 0.247/0.143-0.337) in patients (p=0.013) and leftDVA: 0.136±0.096 (M/IQR: 0.127/0.036-0.176) in healthy vs. 0.258±0.092 (M/IQR: 0.247/0.176-0.301) in patients (p=0.016); BW LogMAR: rightDVA: mean±standard deviation: 0.162±0.097 (M/IQR: 0.159/0.097-0.273) in healthy vs. 0.281±0.130 (M/IQR: 0.273/0.176-0.418) in patients (p=0.047) and leftDVA: 0.156±0.101 (M/IQR: 0.159/0.097-0.198) in healthy vs. 0.298±0.153 (M/IQR: 0.2730/0.159-0.484) in patients (p=0.038)). CONCLUSIONS: Our sensor-based vestibular evaluation system provided a more functionally relevant assessment for the identification of BVH patients.